Rank-DETR for High Quality Object Detection - Pu, Yifan; Liang, Weicong; Hao, Yiduo; Yuan, Yuhui; Yang, Yukang; Zhang, Chao; Hu, Han; Huang, Gao (NeurIPS 2023, 2023)
Modern detection transformers (DETRs) use a set of object queries to predict a list of bounding boxes, sort them by their classification confidence scores, and select the top-ranked predictions as the final detection results for the given input image. A highly performant object detector requires accurate ranking bounding box predictions. For DETR-based detectors, the top-ranked bounding boxes suffer from less accurate localization quality due to the misalignment between classification scores and localization accuracy, thus impeding the construction of high-quality detectors. In this work, we introduce a simple highly performant DETR-based object detector by proposing a set of rank-oriented designs, collectively called Rank-DETR. Our key contributions include: (i) a rank-oriented architecture design that can prompt positive predictions and suppress the negative ones to ensure lower false positive rates, as well as (ii) a rank-oriented loss and matching design that prioritizes predictions of more accurate localization accuracy during ranking to boost the AP under high IoU thresholds.We apply our method to improve the recent SOTA methods (e.g., H-DETR and DINO-DETR) and report strong COCO object detection results when using different backbones such as ResNet-50, Swin-T, and Swin-L, demonstrating the effectiveness of our approach.